A comparative analysis of vacuum assisted closure therapy and conventional dressings: outcomes in chronic diabetic foot ulcers among Indian patients - Singh, Jaskirat; Garg, Varun; Malhotra, Kashish (International Surgery Journal, 2024)
Background: India faces a growing diabetes epidemic, with approximately 77 million individuals affected. Chronic non-healing diabetic foot ulcers (DFUs) are a common complication of diabetes and a major healthcare challenge in Conventional wound care methods often result in prolonged healing times, increasing the risk of infection, hospitalization, and amputations. Vacuum-assisted closure (VAC) therapy, a modern treatment modality, offers a potentially more effective approach to managing these ulcers. Methods: This prospective, observational study was conducted at a tertiary care hospital in India from March 2022 to March 2024. One hundred patients with chronic non-healing DFUs were randomized into VAC therapy or conventional dressing groups. The primary outcomes included wound size reduction and healing time, while secondary outcomes involved patient satisfaction and cost-effectiveness. Results: VAC therapy significantly reduced wound size (65.2% vs. 40.5%) and shortened healing time (6.2 vs. 10.9 weeks) compared to conventional dressings. Additionally, VAC therapy led to higher patient satisfaction and proved more cost-effective due to fewer dressing changes and shorter hospital stays. Conclusions: VAC therapy outperforms conventional dressings in managing DFUs, offering faster healing, better patient satisfaction, and cost-effectiveness. Expanding its use in India could greatly improve diabetic foot care outcomes.